Factors Affecting Customer Loyalty in the Use of Mobile Banking Sharia Bank “X” In Jakarta - Halvon Muslim (Budapest International Research and Critics University, 2022)
This study aims to determine the factors that influence customer loyalty in the use of mobile banking Islamic bank 'X', by applying the theory of diffusion of innovation. The characteristics of innovative technology which include relative advantages, compatibility, perceived risk, and trust are used as antecedent variables to measure customer loyalty in the use of mobile banking. The research uses a quantitative approach with a survey method. The sample is 166 customers who use mobile banking Islamic bank 'X'. Data were collected through questionnaires and analyzed using the SEM – PLS method. The research findings indicate that relative advantage, compatibility, perceived risk, and trust have a significant effect on customer loyalty which is mediated by the variable of using mobile banking. Relative advantage and compatibility are the most powerful and significant factors in the use of mobile banking.